IMPORTANCE OF MEASURING LEVELS OF INFLIXIMAB IN PATIENTS TREATING INFLAMMATORY BOWEL DISEASE IN A BRAZILIAN COHORT - KAMPA,Katia Cristina (2017)
ABSTRACT BACKGROUND: Crohn’s disease and ulcerative colitis are chronic inflammatory bowel diseases. In such pathologies, there is an increased production of alpha tumor necrosis factor (TNF-α). Patients, in whom the conventional immunosuppressant treatment fails, require the use of immunobiological therapy, such as anti-TNF-α, a monoclonal antibody. Infliximab is an anti-TNF-α drug, a chimerical immunoglobulin, with a murine component, which is responsible for the generation of immunogenicity against the drug and formation of anti-TNF-α antibodies. The presence of anti-drug antibodies may be responsible for adverse events and reduction of the drug’s effectiveness. Patients with inflammatory bowel diseases undergoing therapy with biological medication, such as infliximab, can relapse overtime and this may not be translated into clinical symptoms. Thus, there is a need for a method to evaluate the efficacy of the drug, through the measurement of serum infliximab levels, as well as antibodies research. OBJECTIVE: This study aimed to measure serum infliximab levels and anti-infliximab antibodies in patients with inflammatory bowel diseases post-induction phase and during maintenance therapy, and describe the therapeutic modifications that took place based on the serum levels results. METHODS: It was a retrospective study, that included forty-five patients, with a total of 63 samples of infliximab measurement. RESULTS: Twenty-one patients had an adequate infliximab serum level, 31 had subtherapeutic levels and 11 had supratherapeutic levels. Seven patients had their medication suspended due to therapeutic failure or high levels of antibodies to infliximab. CONCLUSION: In conclusion, only a third of the patients had adequate infliximab levels and 36% presented with subtherapeutic levels at the end of the induction phase. Therapy optimization occurred based in about 46% of the samples results, demonstrating the importance of having this tool to help the clinical handling of patients with inflammatory bowel diseases ongoing biologic therapy.